1998
DOI: 10.1152/ajpgi.1998.274.1.g203
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of intestinal barrier function associated with experimental colitis: possible role of mast cells

Abstract: The objective was to characterize changes in barrier and transport function in an experimental model of colitis, and to determine whether mast cells contribute to these changes. Colitis was induced in rats with intracolonic 2,4,6-trinitrobenzenesulfonic acid (TNBS, 30 mg) in 50% ethanol. Controls received 0.9% saline or the ethanol vehicle alone. In vivo loop perfusion was used to assess colonic water flux (in μl ⋅ cm−1 ⋅ h−1) and lumen-to-blood 51Cr-labeled EDTA clearance (% administered dose) after TNBS. Mye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(50 citation statements)
references
References 28 publications
2
46
0
2
Order By: Relevance
“…In our preliminary experiments, we found negative cytotoxic effects of higher concentration of cinnamon essential oil on intestinal cells (Fabián et al 2006). TNBS administration causes extensive colonic damage associated with marked defects in epithelial barrier and changes of intestinal permeability (Stein et al 1998). Huang et al 1993 reported that mucosal permeability increases because of mucosal atrophy in burns and this causes bacterial translocation.…”
Section: Discussionmentioning
confidence: 83%
“…In our preliminary experiments, we found negative cytotoxic effects of higher concentration of cinnamon essential oil on intestinal cells (Fabián et al 2006). TNBS administration causes extensive colonic damage associated with marked defects in epithelial barrier and changes of intestinal permeability (Stein et al 1998). Huang et al 1993 reported that mucosal permeability increases because of mucosal atrophy in burns and this causes bacterial translocation.…”
Section: Discussionmentioning
confidence: 83%
“…MPO levels in the rat small intestine were unchanged 24 h after infection with S. Enteritidis S1400 but were significantly elevated at 72 h. Intestine tissue water content and faecal elastase was also increased at 72 h. This suggests that active recruitment of neutrophils to the intestine (Darwin & Miller, 1999;Stein et al, 1998;Faro et al, 2000;Zimmerman & Granger, 1990;McCormick et al, 1995;Naughton et al, 1996a) may have occurred between 24 and 72 h p.i. These changes would be consistent with the infiltration of polymorphonuclear leukocytes and other inflammatory cells into gut tissue and the release of inflammatory cells into the lumen, previously observed in vivo (Naughton et al, 1995(Naughton et al, , 1996a.…”
Section: Discussionmentioning
confidence: 99%
“…Freeze-dried intestine samples were homogenized (1 : 20, w/v) in ice-cold 0·5 M potassium phosphate (pH 6·0) containing hexadecyltrimethylammonium bromide (HETAB, 5 g l À1 ) and EDTA (3·72 g l À1 ) (Stein et al, 1998;Faro et al, 2000). They were left on ice for 60 min and then centrifuged (3000 g, 30 min, 4 8C).…”
Section: Methodsmentioning
confidence: 99%
“…However, whether balsalazine improves intestinal mucosal permeability is still unknown [15,16] . [17,18] . Therefore, dextran sulfate sodium (DSS)-induced colitis is considered an appropriate model of the injured mucosal barrier [19] .…”
Section: Introductionmentioning
confidence: 99%